2020
DOI: 10.1021/jacs.0c05504
|View full text |Cite
|
Sign up to set email alerts
|

Negatively Curved Nanographene with Heptagonal and [5]Helicene Units

Abstract: Negatively curved nanographene (NG) 4 , having two heptagons and a [5]helicene, was unexpectedly obtained by aryl rearrangement and stepwise cyclodehydrogenations. X-ray crystallography confirmed the saddle-shaped structures of intermediate 3 and NG 4 . The favorability of rearrangement over helicene formation following radical cation or arenium cation mechanisms is supported by theoretical calculations. NG 4 demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
93
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 52 publications
8
93
1
2
Order By: Relevance
“…Even comparing with Rajca's oct‐[5]helicene (72.4°, Figure 1) [29] or the hept‐[5]helicene (77.3°) [10g] the terminal rings of 2 arranged more perpendicularly, showing the great influence of both the position of the octagonal ring in the helicene and the lateral π‐extension in the distortion of the helical moiety (Figure 2 a in gray). On the other hand, we found that the average torsion‐angle of the oct‐[5]helicene is 35.0°, much bigger than that observed for carbo[5]helicene (22.1°) [28] or even a multiple hexapole[5]helicene (22.1–22.2°), [3b–c] thus being comparable to the hept‐[5]helicene (35.6°) [10g] . Furthermore, the maximal dihedral angle in the rim is 79.5°, being one of the largest angles reported so far for a carbo[5]helicene.…”
Section: Resultsmentioning
confidence: 96%
“…Even comparing with Rajca's oct‐[5]helicene (72.4°, Figure 1) [29] or the hept‐[5]helicene (77.3°) [10g] the terminal rings of 2 arranged more perpendicularly, showing the great influence of both the position of the octagonal ring in the helicene and the lateral π‐extension in the distortion of the helical moiety (Figure 2 a in gray). On the other hand, we found that the average torsion‐angle of the oct‐[5]helicene is 35.0°, much bigger than that observed for carbo[5]helicene (22.1°) [28] or even a multiple hexapole[5]helicene (22.1–22.2°), [3b–c] thus being comparable to the hept‐[5]helicene (35.6°) [10g] . Furthermore, the maximal dihedral angle in the rim is 79.5°, being one of the largest angles reported so far for a carbo[5]helicene.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, we found that the angle between the two planes of the terminal rings (Figure 2 a in orange) is exceptionally high (80.8°) when compared to pristine carbo[5]helicene (46°) [28] or even highly strained PAHs with a multiple hexapole [5]helicene (69°) [3b–c] . Even comparing with Rajca's oct‐[5]helicene (72.4°, Figure 1) [29] or the hept‐[5]helicene (77.3°) [10g] the terminal rings of 2 arranged more perpendicularly, showing the great influence of both the position of the octagonal ring in the helicene and the lateral π‐extension in the distortion of the helical moiety (Figure 2 a in gray). On the other hand, we found that the average torsion‐angle of the oct‐[5]helicene is 35.0°, much bigger than that observed for carbo[5]helicene (22.1°) [28] or even a multiple hexapole[5]helicene (22.1–22.2°), [3b–c] thus being comparable to the hept‐[5]helicene (35.6°) [10g] .…”
Section: Resultsmentioning
confidence: 97%
“…As depicted in Figure 1 A, the syntheses of π-extended helicenes 4 and 6 started from dibromo-functionalized 1,2,3,4-tetraphenyl benzene 7 , which was reported in a previous paper. 31 Compound 7 was treated with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) and trifluoromethanesulfonic acid (TfOH) in dry dichloroethane at 30 °C under nitrogen to produce dibromo tribenzo[ fg , ij , rst ]pentaphene 8 as the prefused building block in 49% yield. Compound 8 was then coupled to 2-naphthyl groups by the Suzuki reaction to yield precursor 3 .…”
Section: Resultsmentioning
confidence: 99%